Pembaharuan Pendidikan di Dunia Islam: Geneologi Kemunduran Pendidikan Islam dan Tantangannya vis a vis Modernitas - Iqbal, Lalu Muhammad; Muslim, Asbullah (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study highlights the issue of Islamic education in the modern era, which is often perceived as an exclusive, rigid, and inflexible religion. This phenomenon stems from the history of Islamic education, which has often been hegemonic, creating an image of Muslims that deviates from the core values of Islam, such as love, peace, openness to knowledge, and progress. Islamic teachings, which should be a source of integrated life knowledge, are now more textual and rigid. The decline experienced by Muslims, particularly in the fields of social, political, educational, economic, and intellectual spheres, is often influenced by exclusive and dogmatic attitudes. The aim of this study is to explore the challenges faced by Islamic education in responding to modernity and to examine how Islamic education can be more responsive to he changes of the times. The method used in this study is qualitative research, with data collection techniques through literature review and interviews. Data analysis is conducted using a thematic approach. The findings of the study show that Islamic education needs to adopt a more contextual and flexible approach to religious texts in order to respond to social dynamics and technological progress. The implication of this research is that curriculum and teaching methodology reforms are needed so that Islamic education can produce a more inclusive, progressive, and adaptive generation in facing the challenges of modernity.